Redirecting pantoprazole as a metallo-beta-lactamase inhibitor in carbapenem-resistant Klebsiella pneumoniae - Abdulaal, Wesam H.; Alhakamy, Nabil A.; Asseri, Amer H.; Radwan, Mohamed F.; Ibrahim, Tarek S.; Okbazghi, Solomon Z.; Abbas, Hisham A.; Mansour, Basem; Shoun, Aly A.; Hegazy, Wael A. H.; Abdel-Halim, Mahmoud Saad (Frontiers in Pharmacology, 2024)
The development of resistance to carbapenems in Klebsiella pneumoniae due to the production of metallo-β-lactamases (MBLs) is a critical public health problem because carbapenems are the last-resort drugs used for treating severe infections of extended-spectrum β-lactamases (ESBLs) producing K. pneumoniae. Restoring the activity of carbapenems by the inhibition of metallo-β-lactamases is a valuable approach to combat carbapenem resistance. In this study, two well-characterized clinical multidrug and carbapenem-resistant K. pneumoniae isolates were used. The sub-inhibitory concentrations of pantoprazole and the well-reported metallo-β-lactamase inhibitor captopril inhibited the hydrolytic activities of metallo-β-lactamases, with pantoprazole having more inhibiting activities. Both drugs, when used in combination with meropenem, exhibited synergistic activities. Pantoprazole could also downregulate the expression of the metallo-β-lactamase genes blaNDM and blaVIM. A docking study revealed that pantoprazole could bind to and chelate zinc ions of New Delhi and Verona integron-encoded MBL (VIM) enzymes with higher affinity than the control drug captopril and with comparable affinity to the natural ligand meropenem, indicating the significant inhibitory activity of pantoprazole against metallo-β-lactamases. In conclusion, pantoprazole can be used in combination with meropenem as a new strategy for treating serious infections caused by metallo-β-lactamases producing K. pneumoniae.